Marketing Strategy Analysis Using a Marketing Mix Approach (Case Study of the Giriloyo Batik Bantul Home Industry - Yogyakarta) - Dzulfriansyah, Abid (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research produces further findings regarding the definition of marketing strategy analysis, which involves the use of marketing mix techniques to integrate IFE, EFE, IE, SWOT, and QSPM analysis. To prevent disappointed clients from choosing to patronize other businesses, the front page of the Giriloyo Batik Industry must continue to provide goods and services of the best quality in order to maintain and expand the loyalty, trust and consumer satisfaction that still exists today. In addition, the Giriloyo Batik house industry must improve its management structure to create a positive business environment so that it can develop and develop. Basically, marketing requires quite dominant abilities in marketing through marketing science so that it can make consumers ask questions about Indonesian culture. Therefore, marketing is very necessary when it comes to selling traditional batik. So that marketing in the batik product mix can also circulate in the world through Instagram social media, Indonesian traditional batik product buying and selling groups and national batik events in each region. This makes researchers set a goal to market the batik product mix and be recognized for their work and innovate in terms of the diversity of works that give rise to unique wayang results.